Building resiliency and mitigating climate change – The case of the Unjani Clinic network - Harsha Davé (The Journal of Climate Change and Health)
Introduction: This case study explores the innovative strategies employed by the Unjani Clinic in South Africa to address climate change within the primary healthcare system. By integrating renewable energy and water conservation practices, it highlights the dual role of healthcare providers in climate change mitigation and adaptation, especially in resource-limited settings. Case Presentation: Operational data from annual reports and supplier quotes were analysed to evaluate Unjani Clinic's practices. Currently, 19 % of clinics operate with hybrid or off-grid solar energy systems, reducing utility costs by as much as ZAR 164,512 ($ 9139) and 23, 000 kg carbon emissions. Climate-related disruptions, including flooding and a tornado, significantly impacted clinic operations, underlining the importance of emergency preparedness and network support. Discussion: The Unjani model demonstrates the viability of sustainability efforts to enhance healthcare delivery and environmental resilience. Flexible implementation and leadership support were key enablers. This approach emphasizes the need for aligning investment and policy support to scale such initiatives. Conclusion: The Unjani Clinics (https://www.unjaniclinic.co.za/) provide a replicable model of integrating climate resilience into primary healthcare. This study underscores the critical role of healthcare providers in advancing environmental sustainability and addressing health inequities in vulnerable communities.